Studi etnomedisinal masyarakat Melayu di Kabupaten Tanjung Jabung Barat, Jambi - Siti Susiarti; F.M. Setyowati; J. J. Afriastini (The Ethnobiological Society of Indonesia, 2005)
Study on the Etnomedicinal of Malay society was carried out in the concession area of HTI PT Wirakarya Sakti. This study is a part of a valuation on Non Timber Forest Products (NTFPS) which has been started since 2003. The method employed in this study is